Prevention and management of osteonecrosis of the jaw secondary to bone-targeted therapy in patients with kidney cancer. Issue 3 (September 2016) - Ripamonti, Carla I.; Lucchesi, Maurizio; Giusti, Raffaele
Abstract : Purpose of review: The aim of this revision is prevention and management of osteonecrosis of the jaw (ONJ) secondary to bone-targeted therapy in patients with kidney cancer. Recent findings: Patients with kidney cancer treated with zoledronate suffered from ONJ earlier compared with patients with breast cancer or multiple myeloma; among men, ONJ occurred at 24 months of zoledronic acid treatment in more than 80% of the patients and much earlier, in respect to patients with prostate cancer or multiple myeloma. Protective factors against an ONJ can be sequential prescription of different bisphosphonates and female sex. Less data are available on ONJ secondary to denosumab administration in patients with kidney cancer. Summary: Bone metastases, developing in about 30% of the patients with metastatic renal cell carcinoma, are typically osteolytic on imaging and cause significant morbidity and poor quality of life. Incidence of skeletal-related events has been reported to reach 3.38 per year in such patients. To decrease the incidence of ONJ, a maxillofacial examination must be performed in all patients before treatment with bisphosphonates, in particular in patients with metastatic renal cell carcinoma treated with sunitinib alone or in association with zoledronate. The management of ONJ consider a conservative approach.